Participatory evaluation of chicken health and production constraints in Ethiopia - Sambo, E.; Bettridge, Judy M.; Dessie, Tadelle; Amare, A.; Habte, T.; Wigley, Paul; Christley, Robert M. (Elsevier, 2015)
Chicken production has a major role in the economy of developing countries and backyard production is particularly important to women. Several programmes, in Ethiopia and elsewhere, have attempted to improve chicken production as a means to reduce poverty. A key constraint to chicken production identified by farmers is disease. This study used participatory rural appraisal methods to work with chicken-keepers in order to prioritise chicken diseases, place these within the context of other production constraints, and to explore perceptions of disease risk factors and biosecurity measures. The study, focused on Debre Zeit, Ethiopia, included 71 poultry keepers (41 backyard and 30 semi-intensive chicken producers). Although women played an important role in backyard production systems, semi-intensive farms were more likely to be controlled by men. Participants identified 9 constraints to production: 7 of 8 groups of backyard producers and 15/31 semi-intensive producers ranked diseases as the most important constraint to chicken production. In contrast to previous reports, farmers in both groups had considerable knowledge of diseases and of factors affecting disease risk. Both groups, but particularly semi-intensive producers, highlighted access to feed as a constraint. Many of the challenges faced by both groups were associated with difficulty accessing agricultural and veterinary inputs and expertise. Whilst many of the constraints identified by farmers could be viewed as simply technical issues to be overcome, we believe it is important to recognise the social factors underpinning what are, in reality, relatively modest technical challenges. The low involvement of women in semi-intensive production needs to be recognised by poultry development schemes. Provision needs to be made to allow access to inputs for a wide range of business models, particularly for those, such as women, who have limited access to the capital to allow them to make the jump from backyard to semi-intensive producer, and require support to slowly build up a flock into a profitable venture.